Pendampingan Pengembangan Website Informasi Pesantren Muhammadiyah Banyumas sebagai Media Dakwah Menuju Pesantren Berkemajuan: Assistance in the Development of the Muhammadiyah Banyumas Islamic Boarding School Information Website as a Media for Da'wah Towards a Progressive Islamic Boarding School - Makhful, Makhful; Pratama, Havidz Cahya; Badharudin, Abid Yanuar; Azhar, Afnan Afiatul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to support the Muhammadiyah Banyumas Islamic Boarding School in developing a website as a means of da'wah and information that meets the needs of the digital era. As Islamic educational institutions, Islamic boarding schools play a pivotal role in disseminating Islamic values and fostering communication with the community. However, limited use of information technology often hinders the rapid and effective delivery of information. Therefore, the development of the website https://pontrenmubanyumas.com was carried out as an effort to modernize the Islamic boarding school's da'wah and information media. The implementation method included needs analysis, website management training, technical assistance, and evaluation of website utilization using a Participatory Action Research (PAR) approach. The results showed a measurable positive impact: 90% of participants understood the principles of website management, 85% considered the website's use effective for disseminating information and strengthening da'wah, and 75% experienced increased confidence in managing the website sustainably. This website development is expected to enhance the image of Islamic boarding schools as institutions that are adaptable to technological advancements, expand the reach of da'wah, and strengthen the relationship between the Islamic boarding school and the community. Thus, this website functions as an information media and digital preaching tool that supports the realization of progressive Islamic boarding schools in accordance with Muhammadiyah's vision.